Rules of succession through a focus on everyday life based on the кadiaskers’ notes of the XVII–XVIII centuries - Е. Е. Abibullaeva (Вестник Майкопского государственного технологического университета, 2024)
The goal of the research is to clarify the rules of succession through a focus on everyday life in the Crimean Khanate. The relevance of the research lies in the fact that until now both individual aspects and the general everyday life of the Crimean Khanate have not been studied. In turn, this is due to the fact that the sources of the Crimean Khanate period are mostly written in the Arabic script. Much attention in the article is paid to new facts revealed during the study of the Kadiaskers’ notebooks of the XVII–XVIII centuries. An analysis of the recorded court decisions allowed us to clarify not only one aspect of the extensive legislative system, but also to imagine the everyday life in the Crimean Khanate. When writing the article, the following scientiﬁc-research methods were used: comparative-historical method, linguistic analysis method and others. The identiﬁed examples of court decisions from the Kadiaskers’ notebooks have been transliterated and translated from Arabic (the Ottoman language) into Russian, which will signiﬁcantly facilitate the work for future research. During the research, it has been found out that the executive and legal authorities in the Crimean Khanate worked strictly according to the established Muslim legislative system, the Sharia laws. Each individual example taken and examined reveals the details of life situations and gives an opportunity to look into the everyday life of an ordinary person.